Recurrent primary retro-bulbar hydatid cysts - Kumar, Jayendra (Asian J Neurosurg, 2014)
Retro-bulbar hydatid cysts are extremely uncommon, while nonorbital forms are frequently encountered disease in underdeveloped countries. Most of these are situated in the superolateral and superomedial angle of the orbit. We report a case of recurrent primary hydatid cysts of the orbit, situated in different locations in the orbit. A 35-year-old female patient was admitted to Department of Neurosurgery with proptosis, ptosis and watering from left eye. She also complained for headache with excruciating pain in left eye and loss of vision in left eye. Neurological examination revealed limited ocular mobility in all directions. Visual acuity was reduced to finger counting at 2-feet distance. Papilledema was found in ophthalmic examination. This case was considered as recurrence of primary infection because there was no previous history of hydatid disease and no finding of liver and lung cysts on radiological examinations. Treatment of orbital hydatid cyst, early diagnosis, surgical excision and systemic use of albendazole are suggested.